1985
DOI: 10.1159/000212684
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipolytic Activity of Isolated Adipocytes from Rats throughout Life Span

Abstract: The lipolytic response of isolated adipocytes from 1 ½-, 6-, 24- and 32-month-old rats to various doses of epinephrine was studied. Both the basal and the maximal stimulated glycerol release were largest in the mature rats (6 months old) which had the largest adipocytes. Expressing glycerol release per unit cell surface area (which was drastically reduced with age) eliminated the difference between mature and senescent rats both in absence of epinephrine and at high doses of the hormone. However, at low epinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Moreover, on the basis of fat cell size, a number of conflicting results have been obtained. In some studies, higher rates of stimulated lipolysis were found in large adipocytes than in small ones, 104,229 whereas in other studies, no differences were detected between large and small adipocytes 254,255 . Fatcell size, as well as the mode of expression of the results, has to be carefully taken into account when attempting to analyze the lipolytic responses.…”
Section: The Aging Of the Functioning Fat Cellmentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, on the basis of fat cell size, a number of conflicting results have been obtained. In some studies, higher rates of stimulated lipolysis were found in large adipocytes than in small ones, 104,229 whereas in other studies, no differences were detected between large and small adipocytes 254,255 . Fatcell size, as well as the mode of expression of the results, has to be carefully taken into account when attempting to analyze the lipolytic responses.…”
Section: The Aging Of the Functioning Fat Cellmentioning
confidence: 91%
“…Even in laboratory rodents more suitable to this kind of analysis, data are scanty on the respective roles of hyperplasia and hypertrophy of adipocytes in changes in adipose tissue mass with aging. In the rat, a decline of fatness is noted in old age 92,93,101–104 . If a positive correlation between size of adipocytes and the weight of the body and of the adipose tissue does exist during the growth phase, this correlation is far less evident thereafter 87,93,104–109 .…”
Section: The Structural Development and Aging Of Fat Cells And Adiposmentioning
confidence: 99%
See 3 more Smart Citations